Time-Lapse Photography of Bacillus subtilis L-Forms Replicating in Liquid Medium - Gilpin, Richard W. (1976)
Phase-contrast observations indicate that an L-form of Bacillus subtilis divides in liquid medium by a “budding-like” mechanism without participation of “large bodies” or “elementary bodies.”